The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/0884533616686719
|View full text |Cite
|
Sign up to set email alerts
|

Protein Turnover and Metabolism in the Elderly Intensive Care Unit Patient

Abstract: Many intensive care unit (ICU) patients do not achieve target protein intakes particularly in the early days following admittance. This period of iatrogenic protein undernutrition contributes to a rapid loss of lean, in particular muscle, mass in the ICU. The loss of muscle in older (aged >60 years) patients in the ICU may be particularly rapid due to a perfect storm of increased catabolic factors, including systemic inflammation, disuse, protein malnutrition, and reduced anabolic stimuli. This loss of muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 76 publications
2
40
0
3
Order By: Relevance
“…For adult patients in intensive care units (ICU), complete PN mixtures with a high protein/energy ratio would be recommended [32,33]. Unfortunately, most all-in-one industrialized mixtures generally do not guarantee sufficient AA supply to restore nitrogen losses [22,[34][35][36][37]. In these selected cases, personalized all-in-one PN mixtures represent the best solution to satisfy patient needs and prevent possible complications (i.e., overfeeding or refeeding in case of over-calorie supply).…”
Section: Disease-specific Aa Mixturementioning
confidence: 99%
“…For adult patients in intensive care units (ICU), complete PN mixtures with a high protein/energy ratio would be recommended [32,33]. Unfortunately, most all-in-one industrialized mixtures generally do not guarantee sufficient AA supply to restore nitrogen losses [22,[34][35][36][37]. In these selected cases, personalized all-in-one PN mixtures represent the best solution to satisfy patient needs and prevent possible complications (i.e., overfeeding or refeeding in case of over-calorie supply).…”
Section: Disease-specific Aa Mixturementioning
confidence: 99%
“…32 Isolated EAA such as leucine and its downstream metabolite, β-hydroxy β-methylbutyrate (HMB), have also been used in experimental models of SMM loss (i.e., bed rest/ casting) 21 due to their ability to stimulate MPS 38 and replete the increasing need in muscle protein metabolism observed in states of ageing, inactivity and disease. 16,39 This short, narrative review provides an overview of the latest evidence, with an emphasis on randomised controlled trials known to the authors and available on PubMed, related to the effects of protein supplementation on SMM, strength and function in individuals at risk of muscle wasting disorders, including those residing in long-term care facilities, admitted to hospital, and other clinical populations such as those with chronic obstructive pulmonary disease, heart disease, type 2 diabetes or cancer.…”
Section: Practice Impactmentioning
confidence: 99%
“…14 A hallmark of these states are reduced levels of physical activity or in some cases complete muscle disuse due to illness, surgery or immobilisation. 15,16 Indeed, it has been documented that older adults residing in residential aged care facilities spend approximately 12.5 hours per day sitting or lying, 17 and hospitalised patients may spend about 17 hours a day bed-ridden, 18 which markedly increases the risk of SMM loss. In community-dwelling older adults, 14 days of reduced physical activity in the form of a reduction in the number of steps performed daily (from 5962 ± 695 to 1413 ± 110 steps per day) resulted in a 2.8% loss of leg lean mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for older adults, the WHO had recommended 0.8 g/kg/d since 1985 4 . While the nitrogen balance data that were used for this recommendation indicated higher protein requirements, 5 only recently has expert consensus suggested that protein recommendations for older adults should be higher: 1.0–1.2 g/kg when healthy and up to 1.2–1.5 g/kg when combined with acute disorders, chronic disease, or physical training 7 9 …”
Section: Definition Of Protein Requirements and Application To Intensmentioning
confidence: 99%